2022
DOI: 10.3389/fgene.2022.877522
|View full text |Cite
|
Sign up to set email alerts
|

Chromosomal Rearrangements and Origin of the Multiple XX/XY1Y2 Sex Chromosome System in Harttia Species (Siluriformes: Loricariidae)

Abstract: The Neotropical genus Harttia comprises species with extensive chromosomal remodeling and distinct sex chromosome systems (SCSs). So far, three different SCSs with male heterogamety have been characterized in the group. In some species, the presence of the XX/XY1Y2 SCS is associated with a decrease in diploid numbers and several chromosomal rearrangements, although a direct relation to sex chromosome differentiation has not been shown yet. Here, we aimed to investigate the differentiation processes that have l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 37 publications
2
13
0
Order By: Relevance
“…Karyotype evolution scenarios have been proposed in Harttia , anchoring the chromosomal data to the Harttiini phylogeny ( Blanco et al, 2017 ; Deon et al, 2020 ; Sassi et al, 2020 , 2021 ). In all scenarios, extensive events of chromosomal remodeling have been identified in Harttia , changing the 2n, chromosome morphologies and triggering sex chromosome systems origin independently in each clade ( Blanco et al , 2017 ; Deon et al , 2020 , 2022 ; Sassi et al , 2020 , 2021 ), as also identified in this study.…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…Karyotype evolution scenarios have been proposed in Harttia , anchoring the chromosomal data to the Harttiini phylogeny ( Blanco et al, 2017 ; Deon et al, 2020 ; Sassi et al, 2020 , 2021 ). In all scenarios, extensive events of chromosomal remodeling have been identified in Harttia , changing the 2n, chromosome morphologies and triggering sex chromosome systems origin independently in each clade ( Blanco et al , 2017 ; Deon et al , 2020 , 2022 ; Sassi et al , 2020 , 2021 ), as also identified in this study.…”
Section: Discussionsupporting
confidence: 70%
“…Loricariidae is one of the largest families of freshwater fishes, with over 1,000 valid species grouped in more than 100 genera and distributed throughout South and Central America ( Reis et al, 2003 ; Fricke et al , 2021 ). This family shows a substantial numerical and structural variation in karyotypes, mainly due to Robertsonian rearrangements ( Artoni and Bertollo, 2001 ; Kavalco et al, 2004 ; Ziemniczak et al, 2012 ; Deon et al, 2020 , 2022 ; Sassi et al, 2020 ), making it an outstanding group to investigate evolutionary processes ( Mariotto et al, 2011 ; Barros et al, 2017 ; Glugoski et al, 2018 , 2020 ). In some genera, the reuse of double-strand breaks suggests the occurrence of evolutionary breakpoint regions probable adjacent to rDNAs sites, as proposed for Ancistrus ( Barros et al , 2017 ), Rineloricaria ( Glugoski et al , 2018 ), and Harttia ( Deon et al.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This size is comparable, yet in the higher end, to the genome size of the eight other Siluriformes species reported to date: ∼600 MB for Bagarius yarelli (Jiang et al 2019 ), ~ 700 MB for Pangasionodon hypophtalmus (Kim et al 2018 ), ~ 741 MB for Silurus meridionalis (Zheng et al 2021 ), ∼779 MB for Hemibagrus wyckiodes (Shao et al 2021 ), ~ 800 MB for Silurus glanis (Ozerov et al 2020 ), ~ 900 MB for Clarias batrachus (Li et al 2018 ), ~ 1 GB for Clarias magur (Kushwaha et al 2021 ) and ~ 1 GB for Ictalurus punctatus (Liu et al 2016 ). This result gives no clear support for a whole genome duplication event along the evolution of the Ancistrus lineage, despite the marked chromosome number variation found in this genus and in the family to which it belongs, the Loricariidae (Prizon et al 2016 ; Deon et al 2022 ). Moreover, considering that a recent whole genome duplication would imply finding most genes in two copies, the small proportion of duplicated BUSCOs in the genome of A. triradiatus (only 1.2% of all BUSCOs are duplicated) provides an additional support for the absence of a recent lineage-specific whole genome duplication.…”
Section: Discussionmentioning
confidence: 90%
“…These kinds of ITS were described in species into 12 fish orders ( Ocalewicz, 2013 ). In some groups with chromosomal remodeling, most of the pericentromeric ITS was described as relicts of chromosome fusion events ( Rocco et al, 2001 , 2002 ; Chew et al, 2002 ; Harvey et al, 2002 ; Milhomem et al, 2008 ; Ocalewicz et al , 2009 ; Felippe and Foresti, 2010 ; Mota-Velasco et al, 2010 ; Scacchetti et al, 2011 ; Blanco et al, 2012 , 2017 ; Errero-Porto et al, 2014 ; Favarato et al, 2016 ; Barbosa et al, 2017 ; Barros et al, 2017 ; Glugoski et al, 2018 , 2022 ; Deon et al, 2022a ) or as unstable sites triggering DSBs and chromosome rearrangements ( Rosa et al, 2012 ; Deon et al , 2020 , 2022b ). In other cases, e.g., in some Characidium species, a conserved karyotype with ITS was proposed due to ectopic transposition or events of homologous and non-homologous recombination ( Scacchetti et al , 2015 ; Oliveira et al, 2021a ).…”
Section: Its and Chromosomal Remodeling In Insects And Vertebratesmentioning
confidence: 99%